An Overview of the Director State in Gadolinium Gallate Garnet - Deen, P. P. (Frontiers in Physics, 2022)
shows little sign of abating. Within the field of frustrated magnetism, the compound Gd3Ga5O12 was, for many years, the archetypal frustrated magnet with a ground state that could not be elucidated. In recent years an unusual emergent ground state, a director state, has been determined for Gd3Ga5O12, which is now also observed for other isostructural compounds. In this review an overview of the director state is given, starting with the basics of rare earth magnetism and leading to a summary of the experimental signatures that led to the insight needed to determine the director state.